A Modified 3D-Trench Pixel Detector: Proof of Concept by TCAD Simulations - Boughedda, Abderrezak; Latreche, Saida; Lakhdara, Maya; Dalla Betta, Gian-Franco (Frontiers in Physics, 2022)
A design modification to an existing 3D-trenched pixel detector is proposed, aimed at an improved fabrication yield. The device concept is studied and its performance is evaluated by TCAD simulations, in comparison to the existing one. Although the modified design features a less uniform electric field distribution, it is still expected to yield a very good timing performance and high radiation tolerance, also exploiting charge multiplication effects.